A New Simulation Approach for Performance Prediction of Vertically Integrated Nanogenerators. Issue 6 (2nd May 2018) - Doumit, Nicole; Poulin‐Vittrant, Guylaine
Abstract: The vertically integrated nanogenerator (VING) is one of the most used designs in mechanical energy harvesting using piezoelectric nanowires, due to its easiest manufacturing process. Here, a new modeling approach is presented in order to reduce the computation time of a whole VING finite element simulation. In this work, the effect of the polymer layer (Parylene C), in which nanowires are immersed, on the electromechanical behavior of the whole VING is taken into account. The active part of the VING (nanowires–polymer composite) is considered as a 1–3 piezocomposite. It is formed with ZnO piezoelectric nanowires; however, this study can be applied to any type of piezoelectric nanowires (PZT, GaN, PVDF, etc.) and matrix materials (PDMS, PMMA, Al2 O3, etc.). The present method relies on the finite element method applied to a single nanowire‐composite cell in open‐circuit condition, combined with an analytical modeling of the full VING. This approach allows the computation time to be drastically reduced without inducing significant approximation errors. The expected maximum power, internal capacitance, and optimum resistance can be deduced thanks to this efficient modeling tool, offering wide perspectives for the optimization of such VING devices. Abstract : In this work, an approach of vertically integrated nanogenerator (VING) performance prediction is presented in order to reduce the computation time of a whole VING simulation. This approach relies on a finite element method simulation combined with an analytical modeling of a single nanowire composite cell. The computation time is drastically reduced, while providing the maximum power and optimum resistance of the full VING.